2001
DOI: 10.1002/1529-0131(200106)44:6<1304::aid-art222>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cell death is not a widespread phenomenon in normal aging and osteoarthritic human articular knee cartilage: A study of proliferation, programmed cell death (apoptosis), and viability of chondrocytes in normal and osteoarthritic human knee cartilage

Abstract: Objective Chondrocytes are crucial for adequate matrix balance and function. Cell proliferation and, recently, extensive apoptotic cell death have been reported in osteoarthritic (OA) cartilage. Apoptotic cell death would be an obvious central factor in the initiation and progression of OA, since there is no potential for replacing articular chondrocytes in the adult. Therefore, we studied the occurrence of apoptotic cell disintegration and cell proliferation in OA and normal articular cartilage obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
156
4
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(182 citation statements)
references
References 33 publications
12
156
4
4
Order By: Relevance
“…Although apoptotic chondrocyte death is not always a widespread phenomenon in cartilage aging or OA cartilage degeneration (38), obviously any kind of cell death is detrimental to the tissue. Therefore, any strategy to prevent chondrocyte death or to manipulate the mechanism mediated by stimuli that cause cell death has potential for substantial therapeutic impact (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although apoptotic chondrocyte death is not always a widespread phenomenon in cartilage aging or OA cartilage degeneration (38), obviously any kind of cell death is detrimental to the tissue. Therefore, any strategy to prevent chondrocyte death or to manipulate the mechanism mediated by stimuli that cause cell death has potential for substantial therapeutic impact (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have demonstrated a high rate of apoptosis upon mechanical trauma [41], the role of apoptosis in OA remains controversial [42,43]. While some studies indicated increased rates of apoptosis in OA, linked to proteoglycan depletion from the ECM [44,45], others have shown increased apoptosis only in the calcified cartilage layer [46].…”
Section: αmentioning
confidence: 99%
“…Other markers of cell proliferation such as PCNA, which is an S phase marker, can also be detected during DNA replication and repair, and therefore are not specific for cell division. Ki-67, another cell proliferation marker, is present during the entire cell cycle; its concentration and/ or localization changes during mitotic phases [4,5,11,12], which is when chromosomes are observed and mitosis can therefore be detected. Consequently, the presence of Ki-67 is not necessarily indicative of cell division if it is not associated with chromosomes.…”
Section: Introductionmentioning
confidence: 99%